PENDAMPINGAN UMKM SALE PISANG MELALUI STRATEGI REPACKAGING, REBRANDING, DAN DIGITAL MARKETING: PENDAMPINGAN UMKM SALE PISANG MELALUI STRATEGI REPACKAGING, REBRANDING, DAN DIGITAL MARKETING - asep saepuloh; Yeni Suryani; Halimah Halimah (Universitas Negeri Surabaya, 2023)
The MSME population has grown rapidly after the large-scale social restriction policy was enacted. The existence of MSMEs become an alternative economic solution for the community in running the family economy which had been stopped due to the pandemic. However, of the population, only a few survive, and mostly are going bankrupt. This condition is caused by a lack of entrepreneurial concept and the inability to adapt to technological developments. This community service aims to educate one of the MSME actors in Cibokor village through repackaging, rebranding, and digital marketing strategies. This community service lasts for 4 weeks from July 26 - August 26, 2022 with the method used is entrepreneurship assistance to one of the MSME actors, who is engaged in the production of dried banana fritters, which has been running for a long time but has not experienced significant development. As a result of repackaging and rebranding, the product display has now become more attractive and elegant, meanwhile, marketing that previously only relied on conventional marketing strategies has now switched to using digital marketing through the use of social media and marketplaces.